Socio-hydrological vulnerability and adaptive capacity in Cuajimalpa municipality, Mexico City - Alfie-Cohen, Miriam; Garcia-Becerra, Flor Yunuen; Salinas-Toledano, Mario Alberto; Reyes-Pérez, Javier (Economía Sociedad y Territorio, 2022)
The municipality of Mexico City (CDMX) is facing a situation of socio-hydrological vulnerability (SHV) due to the increasing scarcity of water. This study assesses Cuajimalpa County’s SHV based on the social construction of its space. Water stress and adaptive capacity are key elements for understanding a territory’s material, environmental and social conditions. These elements are approached under an interdisciplinary framework via a mixed methodology that is proposed as an axis for action. The article emphasizes the importance of the knowledge of socio-hydrological vulnerability in specific zones through an interdisciplinary approach as a tool to understand space dynamics and territorial particularity.